2003
DOI: 10.1152/ajplung.00233.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological roles of interleukin-8/CXCL8 in pulmonary diseases

Abstract: Fifteen years have passed since the first description of interleukin (IL)-8/CXCL8 as a potent neutrophil chemotactic factor. Accumulating evidence has demonstrated that various types of cells can produce a large amount of IL-8/CXCL8 in response to a wide variety of stimuli, including proinflammatory cytokines, microbes and their products, and environmental changes such as hypoxia, reperfusion, and hyperoxia. Numerous observations have established IL-8/CXCL8 as a key mediator in neutrophil-mediated acute inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
296
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 396 publications
(315 citation statements)
references
References 144 publications
7
296
0
6
Order By: Relevance
“…On the contrary, we observed that APAP-induced liver injury was markedly attenuated in CXCR2-KO mice with reduced neutrophil infiltration, compared with WT mice, in line with previous reports that CXCR2-KO mice exhibited attenuated neutrophil infiltration in various disease models [16][17][18][19][20][21][22][23][24][25][26][27]. Indeed, Hogaboam and colleagues [38] observed that only a low level of CXCR2 was expressed on untreated hepatocytes and that APAP could enhance CXCR2 protein expression only transiently with a time lag.…”
Section: The Roles Of Ho-1 In Apap-induced Liver Injurysupporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, we observed that APAP-induced liver injury was markedly attenuated in CXCR2-KO mice with reduced neutrophil infiltration, compared with WT mice, in line with previous reports that CXCR2-KO mice exhibited attenuated neutrophil infiltration in various disease models [16][17][18][19][20][21][22][23][24][25][26][27]. Indeed, Hogaboam and colleagues [38] observed that only a low level of CXCR2 was expressed on untreated hepatocytes and that APAP could enhance CXCR2 protein expression only transiently with a time lag.…”
Section: The Roles Of Ho-1 In Apap-induced Liver Injurysupporting
confidence: 92%
“…In contrast, Smith and his colleagues [16] demonstrated that rats treated by anti-neutrophil serum exhibited an enhanced resistance to APAP-induced hepatotoxicity, although they did not explore its mechanisms in detail. Thus, there still remain controversies on the pathogenic roles of neutrophils in APAP-induced liver injury.Neutrophil recruitment is regulated by CXC chemokine ligands (CXCL), murine KC/CXCL1, and macrophage inflammatory protein (MIP)-2/CXCL2 [17,18]. Several lines of evidence demonstrated that the recruitment of neutrophils was significantly reduced in some disease models using mice lacking CXC chemokine receptor 2 (CXCR2), a receptor for CXCL1 and CXCL2 [19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…In addition, bronchial epithelium also directly contributes to immune responses by secreting bioactive substances when exposed to pathogens or stimulation by inflammatory mediators [8]. Among them, interleukin (IL)-8, a member of the CXC chemokine family, plays a pivotal role in regulating neutrophil and monocyte chemotaxis toward sites of infection, and in inducing airway inflammation [9,10]. The presence of microorganisms such as M. catarrhalis in the lower respiratory tract of COPD patients has been found to increase IL-8 release in bronchoalveolar lavage of COPD patients, which is associated with disease progression [11][12][13].…”
mentioning
confidence: 99%
“…Transcriptional regulation of IL-8 is controlled by a tight regulatory signalling network, most importantly involving the nuclear factor (NF)-kB. NF-kB comprises a family of Rel proteins that are normally retained in the cytoplasm by binding to NF-kB inhibitors (IkBs) [9,14]. Following cellular activation, phosphorylation of IkBa results in its ubiquitination and proteolysis, which lead to nuclear translocation and binding to the IL-8 kB-binding site within the il8 promoter [14].…”
mentioning
confidence: 99%
“…CXCR1 and CXCR2 are G protein receptors and have a high affinity for chemokines that are glutamine-leucine--arginine positive (Mukaida 2003, Kim et al 2011). These chemokines have been detected in several human and equine tissues affected by inflammatory conditions associated with severe neutrophil infiltration (Franchini et al 2000, Giustizieri et al 2001, Ainsworth et al 2006, Woodman et al 2006.…”
Section: Introductionmentioning
confidence: 99%